RESTRUCTURING EDUCATIONAL ORGANIZATIONS' MANAGEMENT SYSTEMS IN THE PROCESS OF EDUCATIONAL SERVICES MARKET CORPORATIZATION - O. Kirillova; V. Nikulin (Вестник университета, 2016)
The article discusses some of the features of education system reform, the problems and the new tasks that the modern educational organization faces in the Russian Federation approaches to answer them with the principles of corporate governance.